The Immediate Effect of Swedish Relaxation Massage and Meditation After Mental Fatigue on Dynamic and Semi-dynamic Balance and Lower Extremity Function in Collegiate Female Athletes - Faezeh Gholami; Manouchehr Haidary; Farzaneh Gandomi (Shahid Beheshti University of Medical Sciences, 2023)
Background and Aims Nowadays, Participating in sports activities along with mental fatigue causes musculoskeletal injuries and one of the most important factors in reducing the rate of these injuries is having proper recovery. Swedish relaxation massage and meditation are some of the interventions that can possibly affect people's mental fatigue. Therefore, the purpose of this study was immediate effect of Swedish relaxation massage and meditation after mental fatigue on dynamic and semi-dynamic balance and Lower extremity function in collegiate female athletes.Methods  the current study is a pre-experimental design with pre- and post-test and intervention practices in an experimental group. 16 female athletes aged 20 to 24 years at Razi University were purposefully selected as samples that they were subjected to protocols of mental fatigue (45 minutes of cognitive activity [stroop test]), Swedish relaxation massage (30 minutes) and meditation (30 minutes) with an interval of 48 hours. We were evaluated Dynamic balance with a Y-balance device, semi-dynamic balance with a Lafayette Stability Platform, Lower extremity function with left test. Data analysis was performed using SPSS software, version 22 through paired t-test. Results There was a significant difference between the semi-dynamic, dynamic balance and lower extremity function means in pre-test to post-test, as the means decreased after fatigue (P<0.05). Also, there was a significant difference between post-tests means of semi-dynamic, dynamic balance and lower extremity function between Swedish relaxation massage and meditation (P<0.05).Conclusion In order to prevent injury to athletes, Swedish relaxation massage and meditation can be used as interventions to reduce mental fatigue and improve balance and Lower extremity function.